Adjustment Costs, Irreversibility and Investment Patterns in African Manufacturing - Bigsten, Arne (IMF Working Papers; Working Paper ;, 1999)
This paper examines dynamic patterns of investment in Cameroon, Ghana, Kenya, Zambia and Zimbabwe, assessing the consistency of those patterns with different adjustment cost structures. Using survey data on manufactured firms, we document the importance of zero investment episodes and lumpy investment. The proportion of firms experiencing large investment spikes is significant in explaining aggregate manufacturing investment. Taken together, evidence from descriptive statistics, average investment regressions modeling the response to capital imbalance, and transition data analysis indicate that irreversibility is an important factor considered by firms when making investment plans. The picture is not unanimous however, and some explanations for the mixed results are proposed.